Effect Of Hormonal And Non-Hormonal Treatment On Reproductive Efficiency And Plasma Progesterone, Biochemical And Macrominerals Profile In Postpartum Anoestrus Buffaloes - Parmar, K.H.; Shah, R.G.; Tank, P.H.; Dhami , A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Fifty two postpartum anoestrus Surti buffaloes selected through glynaeco-clinical examinations in three village co-operative societies of Panchmahal district were randomly divided into four groups. Group-A (n=14) was treated with oral supplementation of Chelated mineral mixture @ 30 g/day/ animal for one month, Group-B (n=14) with Inj. inorganic phosphorus and Inj. vitamin AD3E 10 ml each, im at weekly interval for three consecutive week, Group-C (n=12) with Inj. GnRH (Receptal) 5.0 ml, im once and Group-D (n=12) served as untreated control. The effect of above treatments on reproductive efficiency and plasma profile of progesterone and various biochemical and macro minerals was studied at pre-treatment, at induced oestrus and 22nd day post-AI. Significantly higher oestrus induction response (83.33%), the highest conception rate (80.00 %) and reproductive efficiency (66.66 %) were observed for group-C GnRH treated buffaloes followed by group-B and A, and the values were lowest in control group-D. The mean plasma progesterone (ng/ml) levels were significantly (P<0.05) higher at day 22nd post-AI in all the groups compared to those at pre treatment and induced oestrus phase. The mean plasma protein level was significantly (P<0.05) higher at induced oestrus and 22nd day post-AI than at pre-treatment level in group-A (7.25 ± 0.22 and 7.31 ± 0.18 Vs 6.52 ± 0.31 g/dl). The mean total cholesterol levels (mg/dl) were non-significantly higher at induced oestrus and 22nd day post-AI than at pre-treatment level in all the groups. Plasma calcium levels were significantly (P<0.05) higher at induced oestrus and 22nd day post-AI than that at pretreatment level in group-B. Similarly the mean plasma inorganic phosphorus level was significantly higher at induced oestrus than the pre-treatment level in group-A. The mean plasma calcium and inorganic phosphorus levels at different stages showed non-significant differences in buffaloes of other groups. Results showed that, injection of GnRH had beneficial effect on reproductive performance of postpartum anoestrus buffaloes as compared to vitamin-mineral supplementation.